Towards High‐Mobility Heteroepitaxial β‐Ga2O3 on Sapphire − Dependence on The Substrate Off‐Axis Angle. Issue 2 (22nd November 2017) - Rafique, Subrina; Han, Lu; Neal, Adam T.; Mou, Shin; Boeckl, John; Zhao, Hongping
Abstract : This paper presents the heteroepitaxial growth of β‐Ga2 O3 thin films on off‐axis (0001) c‐sapphire substrates by low pressure chemical vapor deposition (LPCVD). (−201) oriented β‐Ga2 O3 thin films are grown using high purity metallic gallium (Ga) and oxygen (O2 ) as the precursors. N‐type conductivity in silicon doped β‐Ga2 O3 thin films is demonstrated. It is found that the film crystalline quality, surface morphology, and electrical conductivity are remarkably sensitive to the off‐axis angles. X‐ray phi‐scan measurements of the β‐Ga2 O3 film grown on on‐axis c‐sapphire indicate the presence of six in‐plane rotational domains due to the substrate symmetry. With the increase of off‐axis angle toward <11–20> of sapphire, one of the in‐plane orientations is strongly favored. The use of off‐axis substrate also reduced the X‐ray rocking curve full width at half maximum and increased the intensities of the Raman peaks. The best electrical properties of the β‐Ga2 O3 film are exhibited by the film grown on 6° off‐axis c‐sapphire. The room temperature electron Hall mobility was 106.6 cm 2 V −1 s −1 with an n‐type carrier concentration of 4.83 × 10 17 cm −3 . The results from this study demonstrate high electrical quality β‐Ga2 O3 thin films grown on off‐axis c‐sapphire substrates, which are promising for high power electronic and short wavelength optoelectronic device applications. Abstract : This paper studies the heteroepitaxial growth of Si doped β‐Ga2 O3 thin films on off‐axis c‐sapphire substrates by low pressure chemical vapor deposition (LPCVD). The figure shows the temperature dependence of the electron Hall mobility for the Si doped β‐Ga2 O3 thin films grown on substrates with different off‐axis angles (Δa =0°, 3.5°, and 6°). The film grown on substrate with 6 ° off‐axis angle shows the best electrical properties with peak mobility of ∼238 cm 2 V −1 s −1 (at 87 K), room‐temperature mobility of ∼85 cm 2 V −1 s −1, and room‐temperature carrier concentration of 5 × 10 17 cm −3 .